Development of Content Differentiated Blended Learning Model with Media Learning Management System to Improve Critical Thinking Skills - Wahyudi, Sigit; Joyoatmojo, Soetarno; Hindrayani, Aniek; Indriayu, Mintasih; Totalia, Salman Alfarisy; Sa’adah, Silky Roudhotus (Journal of Ecohumanism, 2024)
Critical thinking skills will help students solve problems, both simple difficulties and issues that are highly complex. Students must possess critical thinking skills because the ability to solve problems that are right, logical, and fast in critical thinking skills will help students prepare themselves to face personal and career challenges in the future. This study aims to design a content-differentiated blended learning model with a media learning management system to improve the critical thinking skills of high school students in high school economics. This study uses the Design-Based Research (DBR) method aimed at grade XI students of State Senior High Schools in Sukoharjo. The study subjects were economics teachers at State Senior High Schools in Sukoharjo and 143 State Senior High School students in Sukoharjo. The study results showed that students’ critical thinking skills had increased from the first cycle of implementation to the second cycle. The analysis results were found in observations during learning using the Content Differentiated Blended Learning model with the Media Learning Management System.